Addition of different concentrations of prostasome‐like vesicles at neutral or slightly alkaline pH decreases canine sperm motility. (27th September 2016) - Zelli, R.; Orlandi, R.; Verstegen, J.; Troisi, A.; Elad Ngonput, A.; Menchetti, L.; Cardinali, L.; Polisca, A.
Summary: Prostasome‐like vesicles (PV) are components of the canine prostatic fluid during ejaculation and despite some enzymatic activities have been identified recently, their functions in the reproductive events in this species are still poorly understood. In this study, we evaluated at neutral or slightly alkaline pH, the effects of different concentrations of purified PV on sperm cell motility characteristics and the impact on the short‐ and long‐term preservation of preserved semen maintained at room temperature. Two different experiments were performed. In the first experiment, purified PV were added at increasing concentration (1.25, 2.5, 5, 10, and 20 μL equivalent to 1, 2, 4, 8, and 16 μg of protein, respectively) to aliquots of 100 μL of preserved semen maintained at 22 °C at the following time points: 0, 30, 60, 120, 240, and 480 min. Computer‐assisted sperm motility characteristics and pH were assessed three times at each time points, for each sample and for every concentrations. In the second experiment, the purified PV were added with the same methods as described above but only at time 0. Sperm motility characteristics and pH were assessed over the time. This study showed how the addition of purified PV to preserved semen affects negatively ( p < 0.05) at neutral and alkaline pH, both total and progressive motility in a concentration depending manner. Furthermore, prostasome addition was demonstrated to change the quality of sperm movement which may represent a mechanism facilitating sperm cells attachment to the uterine epithelium and facilitating energy preservation before fertilization.